LINGUISTIC DIPLOMACY: THE ROLE OF KOREAN LANGUAGE IN INDONESIA–SOUTH KOREA RELATIONS - Darmanto, Darmanto; Cahyo, Eko Nur; Nengrum, Yeny Septi; Adefiannisa, Fitra Jasmine (Jurnal Multidisipliner Bharasumba, 2025)
In the context of globalization, the Korean language has emerged as a strategic asset in Indonesia, especially in labor mobility, academic exchange, and cultural diplomacy. This study explores how Korean language education enhances Indonesia–South Korea relations by enabling Indonesian workers to access employment through the Employment Permit System (EPS) and facilitating academic opportunities via scholarships and university partnerships. The Korean Wave (Hallyu) further fuels interest in the language, especially among youth, aligning cultural fascination with professional aspirations. Despite its growing prominence, challenges such as unequal access, limited qualified teachers, and high costs hinder equitable implementation. By adopting a qualitative methodology and analyzing secondary data, this paper argues for stronger policy support, digital solutions, and bilateral cooperation to expand language education. Ultimately, Korean language learning fosters mutual understanding, soft power, and long-term collaboration between Indonesia and South Korea.